2013
DOI: 10.1055/s-0033-1357504
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis and Thrombophilia: A Systematic Review and Meta-Analysis

Abstract: Cerebral venous thrombosis (CVT) is a rare manifestation of venous thromboembolism (VTE) and stroke. The aim of our systematic review was to provide an updated summary of the strength of association between CVT and thrombophilia and to explore the relevance of thrombophilia for recurrence of CVT or other VTE, or other outcome variables. MEDLINE (via PubMed), EMBASE (via Ovid), and CENTRAL were systematically searched, including references of retrieved articles. Cohort studies of ≥ 40 patients and case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…In patients with cerebral venous thrombosis we found only a significantly higher frequency of the FII G20210A variant respect to the GP, and such data match with two studies [2,30]. While, our data exclude a role of MTHFR and FVL variants that in previous studies had been reported to be associated to a higher risk for the CVT [30,31]. Interestingly, also in CVT (as we observed in PVT) the frequency of FII G20210A is higher in females than in males.…”
Section: Discussionsupporting
confidence: 90%
“…In patients with cerebral venous thrombosis we found only a significantly higher frequency of the FII G20210A variant respect to the GP, and such data match with two studies [2,30]. While, our data exclude a role of MTHFR and FVL variants that in previous studies had been reported to be associated to a higher risk for the CVT [30,31]. Interestingly, also in CVT (as we observed in PVT) the frequency of FII G20210A is higher in females than in males.…”
Section: Discussionsupporting
confidence: 90%
“…Another study indicates that changes in cerebral blood flow correlate better with the mean flow velocity in the basal vein than with arterial flow velocities (Mursch et al, 2001). Besides the thrombophilia after stroke, other brain disorders has been reported to have a strong association with cerebral venous thrombosis (Lauw et al, 2013). Therefore, the venous system is an important contributor for ischemic event after acute brain injury.…”
Section: Vein-mediated Pathophysiology After Acute Brain Injurymentioning
confidence: 99%
“…Cerebral venous thrombosis is rare thrombotic condition commonly associated with the presence of thrombophilia[ 1 ]. Prothrombin G20210A is one of the most common thrombophilias associated with venous thrombosis, including cerebral venous thrombosis[ 2 ]. In patients with deep vein thrombosis or pulmonary embolism the prevalence of prothrombin G20210A is highly dependent on the country of origin or ethnicity [ 3 – 7 ] but this variation has not been evaluated in patients with cerebral venous thrombosis.…”
Section: Introductionmentioning
confidence: 99%